TINGKAT PENGETAHUAN IBU HAMIL TENTANG BUKU KIA BERDASARKAN TINGKAT PENDIDIKAN DAN PEKERJAAN - ely tjahjani (Akademi Kebidanan Griya Husada Surabaya, 2016)
Introduction: The MCH Handbook is a tool for early detection of maternal and child health problems or problems, communication and counseling tools with information that is important for mothers, families, and communities regarding maternal and child health services. The MCH Handbook is useful as a complete health record from pregnant women to 5 year old children. Pregnant women are expected to have good knowledge about KIA books. The factors that influence maternal understanding include: attitude, education, and work. This study aims to describe the knowledge of pregnant women about MCH books based on their level of education and employment. Method: This study included descriptive research. Population 148 people, sample 73 people taken by Non Probability Sampling with accidental sampling technique. Data retrieval uses primary data, namely questionnaire. Results: The results of the study showed that the majority of low-educated pregnant women were 47.94%, the majority of pregnant women were unemployed at 63.01%, and it was concluded that the majority of non-working mothers had less knowledge (54.35%), compared to working mothers. amounting to (18.52%). Discussion: From the results of the study it was concluded that there were still many pregnant women who had low knowledge about the KIA book. To increase the knowledge of pregnant women, it is our duty as health workers to introduce, provide information, and use MCH books in health services for mothers and children.